Development and psychometric properties of a measurement to ascertain the impact of genitourinary symptoms on health-related quality of life in menopausal women: the Cervantes-GSM questionnaire. Issue 5 (12th May 2023) - Baquedano, Laura; Rejas-Gutiérrez, Javier; Coronado, Pluvio J.
Abstract : This study presents a novel questionnaire capable of assessing Health-Related Quality of Life in menopausal women with genitourinary syndrome of menopause. The tool has shown acceptable preliminary psychometric properties, including feasibility, factor structure, construct validity, and internal consistency. Abstract: Objective: The Cervantes-GSM questionnaire is a novel tool currently being developed to examine the impact of genitourinary symptoms on health-related quality of life in adult women with genitourinary syndrome of menopause (GSM). Methods: A literature review and cognitive debriefing were conducted in women with GSM, which provided the basis for creating a draft questionnaire. This draft version was pilot-tested to check participant comprehension and ease of completion. The initial draft was then refined to obtain a 15-item version with five domains whose initial psychometric properties were analyzed in 130 adult women with GSM. The psychometric properties tested in this study were factorial structure, feasibility, reliability, and construct validity. Results: The Cervantes-GSM 15-item questionnaire consists of five domains: vulvovaginal symptoms, urinary symptoms, psychological (emotions), interference with daily activities, and sexuality. The instrument was shown to be feasible and easy to complete, regardless of age or educational level. Internal consistency was high (Cronbach α = 0.88). Construct validity was supported by convergent-divergent validity showing higher correlation coefficients between items in their own domain (>0.70) than with the other items and domains in the questionnaire. Cervantes-GSM also showed known group validity with significant differences in total score and most domains (13-20 points, P < 0.01) regardless of whether women chose local treatment of their genitourinary symptoms. Conclusion: This study presents a novel questionnaire capable of assessing health-related quality of life in menopausal women with GSM. The tool has shown acceptable preliminary psychometric properties, including feasibility, factor structure, construct validity, and internal consistency.